“El lenguaje iconográfico para el desarrollo de la expresión oral en los niños de 4 años del centro de educación inicial “Dr.Camilo Gallegos Toledo”, parroquia Lizarzaburu, cantón Riobamba, provincia de Chimborazo, año lectivo 2015-2016. - Calle Astudillo, Carmen Ofelia (2017)
The present investigation was carried out the Initial Education Center “Dr. Camilo Gallegos Toledo” with the proposal of identifying the theoretical-methodological application of the iconographic language that through the reading of images the child acquires artistic skills, increases visual capacity, imagination, creativity, fantasy and improve the vocabulary with new words and better structured sentences through activities such as painting, collage, drawing, cards explanation, storytelling. The use of images in initial education is a dynamic pedagogical resource that attracts children´s attention and motivates them to communicate by describing them. These actions are important because they mark the beginning of reading and writing. The work was carried out with a population of 32 children aged 4 years. This researching methodology is based on the non-experimental, descriptive, field´s study and bibliographic method; In addition to this, the observation technique was used for date collection. After the diagnosis it was demonstrated that the iconographic language offers opportunities to discover that it produces emotions of well-being and the children enjoy building their own ideas of the world and acquire a cognitive development.